Statistical survey of economy of Japan. - Japan. Ministry of Foreign Affairs ([Tokyon] Ministry of Foreign Affairs, Japan, 1968)
Annual
Keywords: Japan -- Economic conditions -- 1945- -- Statistics -- Periodicals